Pemanfaatan Media Sosial Instagram Pada Kampanye “Traditional Games Returns” (Faculty of Communications Science, Dr. Soetomo University, 2019)
Traditional Games Returns (TGR) is a non-profit community that the mission is to restore and introduce Indonesian traditional games. This counted as the asset and cultural heritage to preserve national identity. Along with the development of technology, traditional games are now rarely played. Thus, TGR Community campaigned through Instagram to grab its target which is digital generation. This study will reveal how TGR as a community utilizes social media according to the perspective of information, community and action (Lovejoy and Saxton, 2012) as well as qualitative approach. The result showed that TGR used public figures for message effectiveness and credibility. Then TGR created interactive and creative content such as nostalgic values, and involved participation from netizens by making competitions and utilizing hashtag feature. Suggestions for further research is dig more deeper about creative strategies in content creation, this is actually main factor in attracting potential and main followers to participate, that makes non-profit organization survive. Keywords: Media Social Utilization, Instagram, Community, Digital Campaign